Postponement of Inheritance Distribution from an Islamic Legal Perspective - Devi Kasumawati; Ahmad Manfaluti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The context of this research is the prevalent practice of delaying the distribution of inheritance for an indefinite period in South Kalimantan Province. Consequently, the objective of this study is to examine this phenomenon from the perspective of Islamic law. This research is included in the type of qualitative normative research, starting from the legal behavior of the South Kalimantan Muslim community which is then studied within the scope of Islamic legal normativism. The data source used is secondary data, including primary legal materials and secondary legal materials. The data collection technique uses the documentation method. The analysis indicates that the postponement of inheritance distribution is not necessarily haram, as there is no specific substantiation in the Qur'an or hadith texts regarding the time limit for inheritance distribution. Additionally, there are numerous regulations that can validate the practice of delaying the distribution of inheritance, such as the principle of لِلْوَسَائِلِ حُكْمُ الْمَقَاصِدِ , which maintains that the law of the means of an action is equivalent to the law of the action. Therefore, the law of postponing the distribution of inheritance is relative and dependent upon the purpose or consequences of the delay.